Publicly Funded, Pegylated Interferon-Alpha Treatment in British Columbia: Disparities in Treatment Patterns for People with Hepatitis C - Priscilla C Hsu; Jane A Buxton; Andrew W Tu; Warren D Hill; Amanda Yu; Mel Krajden (Canadian Journal of Gastroenterology)
BACKGROUND: An estimated 60,000 British Columbians are chronically infected with the hepatitis C virus (HCV); 10% to 20% will develop cirrhosis after 20 years and 5% to 10% of these will develop hepatocellular carcinoma. Although treatment may prevent cirrhosis and liver cancer, and improve quality of life, availability is limited.